Program Perpustakaan dalam Mengatasi “Library Anxiety” - Sari, Dita Indah; Sayekti, Retno (Librarianship in Muslim Societies, 2023)
Libraries are valuable assets in the acquisition of knowledge, but often individuals, especially students, face "library anxiety", which creates feelings of tension, fear, and helplessness while in the library. This condition is common and can hinder academic performance. This study aims to determine the factors of Library Anxiety and library programs as an effort to overcome Library Anxiety at UIN Syarif Hidayatullah Library Center Jakarta, using Constance Mellon's Library Anxiety Theory. The method used in this research is a qualitative method with a case study approach. Data collection techniques were conducted through interviews, observation, documentation and literature review. The results showed that factors cause Library Anxiety at UIN Syarif Hidayatullah Library Center Jakarta, including the size of the library building. These users need to learn where library services and facilities are, how to start activities in the library and what can be done there. To overcome this, UIN Syarif Hidayatullah Library Center has several library programs, including Library orientation, information guidance, library program socialization, and information literacy workshops. This research contributes to library and information science by identifying the causes of Library Anxiety and analyzing the programs implemented to overcome this anxiety at UIN Syarif Hidayatullah Library Center Jakarta. The results of this study can assist libraries and information managers in developing more effective strategies to support users and overcome the challenges of Library Anxiety.